Beispiel Nr: 02
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 9 x +5 + 4 z=13\\ 6 x +3 y + -5 z=17\\ 3 x -10 y + 6 z=23\\ \\ \\ \textbf{Rechnung:} \\\small \begin{array}{l} 9x+5y+4z=13 \\ 6x+3y-5z=17 \\ 3x-10y+6z=23 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline9 & 5 & 4 & 13 \\ 6 & 3 & -5 & 17 \\ 3 & -10 & 6 & 23 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}2=\text{Zeile}2\cdot 9\text{-Zeile}1\cdot 6 \\z2s1=6\cdot 9-9\cdot 6 =0 \\ z2s2=3\cdot 9-5\cdot 6 =-3 \\ z2s3=(-5)\cdot 9-4\cdot 6 =-69 \\ z2s4=17\cdot 9-13\cdot 6 =75 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline9 & 5 & 4 & 13 \\ 0 & -3 & -69 & 75 \\ 3 & -10 & 6 & 23 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot 9\text{-Zeile}1\cdot 3 \\z3s1=3\cdot 9-9\cdot 3 =0 \\ z3s2=(-10)\cdot 9-5\cdot 3 =-105 \\ z3s3=6\cdot 9-4\cdot 3 =42 \\ z3s4=23\cdot 9-13\cdot 3 =168 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline9 & 5 & 4 & 13 \\ 0 & -3 & -69 & 75 \\ 0 & -105 & 42 & 168 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-3)\text{-Zeile}2\cdot (-105) \\z3s2=(-105)\cdot -3-(-3)\cdot (-105) =0 \\ z3s3=42\cdot -3-(-69)\cdot (-105) =-7,37\cdot 10^{3} \\ z3s4=168\cdot -3-75\cdot (-105) =7,37\cdot 10^{3} \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline9 & 5 & 4 & 13 \\ 0 & -3 & -69 & 75 \\ 0 & 0 & -7,37\cdot 10^{3} & 7,37\cdot 10^{3} \\ \end{array} \\ \\ z=\frac{7,37\cdot 10^{3}}{-7,37\cdot 10^{3}}=-1\\y \cdot (-3)+(-69)\cdot-1=75\\y= -2\\x\cdot 9+5\cdot-2+4\cdot(-1)=13\\x= 3\\L=\{3/-2/-1\}$